Gestión de efluentes líquidos generados en la planta de harina y aceite de pescado, de la empresa corporación pfg - centinela s.a.c. para su evaluación y dictamen respectivo, a efecto de obtener el título de ingeniero químico. - Espinoza Goicochea, Juan Carlos (2014)
In Peru the first attempts in fishmeal production, was since year 1949 from the fish waste, it was only in 1951 the production of fish meal using fresh anchovies as feedstock. The fishing industry in Chimbote starts in 1954, reaching a total of 48 industrial plants in 1998; since its initiations the operation of these plants has been associated with the generation of effluents at the different stages of the process, such: water of pumping, blood water, tail water, water the cleaning of equipment, among others, the which were dumped without any treatment at sea, causing negative impacts its ecosystem. The bay “El Ferrol” is considered one of the most polluted bays of Peru, as a result of fishmeal industry, the which develops from the 60s; so since 2002 the Multisectoral Technical High Commission in charge was set to propose Environmental Recovery Plan bay El Ferrol, and declares of national interest the comprehensive solution of the problems of pollution and destruction of El Ferrol bay. The Industry the fishmeal and fishoil has been growing in recent years in the Peru in technology, innovation, research and development using tools the engineering, bio-engineering, chemistry, electronics, mechanics, and other sciences and branches available; all this as a result of the requirement of a constantly changing globalized market; associated with this work of optimizing in the use of resource, to been increasing since many years ago a constant concern for the care of the environment and this include the negative impact that cause over the sea, to because for the discharge of effluents generated by the operation of these fishmeal plants, accompanied the publication of legal regulations in force in relation to the environment; this concern for the environment has globalized and there is a participation of the interested part: company, government, population and clients. The management of effluents generated by the operation of the plant Fishmeal and fishoil, starts from the study of the raw matter, the description of the different absorbing systems for unloading of fish and its influence on the value of flow water of pumping and destruction fish, study the different stages of treatment and technology available to do so, up management tools that develops the Company (Water Balances, PACPE, PAMA, EIA, etc).